Golput Perspektif Undang-Undang Nomor 7 Tahun 2017 Tentang Pemilihan Umum dan Siyasah Dusturiyah - Habibah, Habibah; Adan, Hasanuddin Yusuf (Politica: Jurnal Hukum Tata Negara dan Politik Islam, 2024)
Abstention is indirectly related to feelings of distrust towards potential leaders or contesting political parties. Golput is also often seen as a form of protest or dissatisfaction with the political system. This research examines the legal review of abstention from the perspective of the laws of the Republic of Indonesia and perspective of siyasah dusturiyah. The research method used is library research with a qualitative approach. The data source used is based on the results of a review of Law no. 39 of 1999 concerning human rights, Law no. 7 of 2017 concerning the holding of general elections, as well as the 2009 MUI Fatwa and opinions from contemporary ulama. The results of the research show that Indonesian legislation states that abstention is a constitutional right granted by the government to the people. so that the people have authority over voting rights and are allowed to exercise these rights or not. Meanwhile, from the siyasah dusturiyah perspective, choosing a leader is obligatory. If all Muslims in Indonesia abstain from voting then they are sinning, because the law requires fardu kifayah. Abstentions have the potential to give unqualified or unfit people the chance to become leaders. So it gives rise to mafsadat against Islamic law. However, in conditions where Muslims live in non-Muslim countries, abstention is recommended because it does not give loyalty or trust to the wrong people.